(untitled) (Economic studies journal, 2024)
The study aimed to identify digital marketing and its relationship to mental image. From the point of view of Al-Madar Al-Jadeed Company’s customers, the researchers used the descriptive analytical approach, and the questionnaire was used as a tool for collecting data, distributing (60) questionnaires, and retrieving (50) that can be analysed. The results of the study showed that there is a statistically significant relationship between digital marketing on the mental image and that there is an application For digital marketing in terms of attraction, communication, and retention, there is no application of digital marketing in terms of engagement and learning at Al Madar Company.